Validity and Realibility of Chemistry Systemic Multiple Choices Questions (CSMCQs) - Erfan Priyambodo; Marfuatun Marfuatun (Institute of Advanced Engineering and Science, 2016)
Nowdays, Rasch model analysis is used widely in social research, moreover in educational research. In this research, Rasch model is used to determine the validation and the reliability of systemic multiple choices question in chemistry teaching and learning. There were 30 multiple choices question with systemic approach for high school student class XI. In this research, a 164 student as the subject of the research. The data was collecting during March – April 2015. The data was analysis using Winsteps application with Rasch model. The reseach shows that 29 question of 30 questions was valid through Rasch model analysis. The reliability of systemic multiple choices question was 0.93, which is very good chategory.